1995
DOI: 10.1021/bi00046a006
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the MutT Enzyme, a Nucleoside Triphosphate Pyrophosphohydrolase

Abstract: The MutT enzyme (129 residues) catalyzes the hydrolysis of normal and mutagenic nucleoside triphosphates, such as 8-oxo-dGTP, by substitution at the rarely attacked P-P, to yield NMP and pyrophosphate. Previous heteronuclear NMR studies of MutT have shown the secondary structure to consist of a five-stranded mixed P-sheet connected by the loop I-a-helix I-loop I1 motif, by two tight tums, and by loop 111, and terminated by loop IV-a-helix I1 (4) restraints and 34 backbone hydrogen bond restraints were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(131 citation statements)
references
References 41 publications
(67 reference statements)
7
124
0
Order By: Relevance
“…It therefore seems that recombinant YSA1H migrates anomalously on SDS\PAGE. This phenomenon of slower migration has been observed with other MutT motif proteins, including human Ap % A hydrolase [6] and S. cere isiae Ap ' A hydrolase [18] and might result from incomplete denaturation and SDS binding during sample preparation owing to the stability imparted by the mixed β-sheet core structure that might be a feature of this enzyme family [23]. (Figure 6b, lane 3).…”
Section: Size and Presence Of Ysa1h Protein In Human Cell Extractssupporting
confidence: 57%
“…It therefore seems that recombinant YSA1H migrates anomalously on SDS\PAGE. This phenomenon of slower migration has been observed with other MutT motif proteins, including human Ap % A hydrolase [6] and S. cere isiae Ap ' A hydrolase [18] and might result from incomplete denaturation and SDS binding during sample preparation owing to the stability imparted by the mixed β-sheet core structure that might be a feature of this enzyme family [23]. (Figure 6b, lane 3).…”
Section: Size and Presence Of Ysa1h Protein In Human Cell Extractssupporting
confidence: 57%
“…For E. coli MutT, it has been established that the 23-residue sequence constitutes the active center for dGTPase activity (21,32), probably also for the 8-oxo-dGTPase activity, and that the module consists of loop I (Gly 37 -Thr 45 ) and ␣-helix I (Pro 46 -Gly 59 ) (33). The ␣-helix I in MutT is apparently amphipathic, and it was shown that MutT has two hydrophobic cores, one of them consisting of Val , and Lys 39 may be involved in the catalytic reaction (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Nudix proteins are all characterized by the presence of a highly conserved 23-residue 'Nudix box', GX 5 EX 7 REUXEEXGU, where U is a bulky hydrophobic group and X is any residue (Abeygunawardana et al, 1995;Bessman et al, 1996). The Nudix sequence adopts a loop-helix-loop motif (Koonin, 1993) that serves to coordinate the catalytically essential divalent cation (usually Mg 2+ ) to the protein (Lin et al, 1997;Bailey et al, 2002;Gabelli et al, 2001).…”
Section: Figurementioning
confidence: 99%
“…1. It is from this general structure, Nucleoside diphosphates linked to some other moiety x, that the acronym 'Nudix' arose (Abeygunawardana et al, 1995;Bessman et al, 1996). Identified Nudix substrates include capped mRNA (Wang, Jiao et al, 2002), dinucleotide coenzymes, nucleotide sugars, nucleotide alcohols, dinucleotide polyphosphates, both canonical and oxidized (deoxy)ribonucleoside triphosphates (NTPs) (Dunn et al, 1999) and canonical (deoxy)ribonucleoside diphosphates (NDPs) (Fisher et al, 2004;Buchko et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation